Replication of Vectored Herpesvirus of Turkey (HVT) in a Continuous, Microcarrier-Independent Suspension Cell Line from Muscovy Duck - Karoline Mähl; Deborah Horn; Sirine Abidi; Benedikt B. Kaufer; Volker Sandig; Alexander Karlas; Ingo Jordan (Vaccines, 2025)
Background/Objectives: More than 33 billion chickens are industrially raised for meat and egg production globally and vaccinated against Marek’s disease virus (MDV). The antigenically related herpesvirus of turkey (HVT) is used as a live-attenuated vaccine, commonly provided as a recombinant vector to protect chickens against additional unrelated pathogens. Because HVT replicates in a strictly cell-associated fashion to low levels of infectious units, adherent primary chicken or duck embryo fibroblasts are infected, dislodged from the cultivation surface and distributed as cryocultures in liquid nitrogen to the site of application. Although viable cells are complex products, application of infected cells in ovo confers protection even in presence of maternal antibodies. Methods/Results: The aim of our study was to determine whether a continuous cell line in a scalable cultivation format can be used for production of HVT-based vaccines. The AGE1.CR cell line (from Muscovy duck) was found to be highly permissive in adherent cultures. Propagation in suspension, however, initially gave very low yields. The induction of cell-to-cell contacts in carrier-independent suspensions and a metabolic shock improved titers to levels suitable for vaccine production (>105 infectious units/mL after infection with multiplicity of 0.001). Conclusions: Production of HVT is challenging to scale to large volumes and the reliance on embryonated eggs from biosecure facilities is complex. We demonstrate that a cell-associated HVT vector can be propagated in a carrier-independent suspension culture of AGE1.CR cells in chemically defined medium. The fed-batch production is independent of primary cells and animal-derived material and can be scaled to large volumes.